PENGENALAN WARNA KUNING TELUR AYAM KAMPUNG SETELAH MENGALAMI PROSES PERLAKUAN PEREBUSAN - Masdania Zurairah; Rizkha Rida; Margie Subahagia Ningsih; Asmara Sari Nasution (JURNAL PENGABDIAN MANDIRI, 2024)
A service has been carried out at the Layar Dakwah Foundation regarding the color of egg yolk from free-range chicken eggs, with a heating time of 3 minutes after the boiled water boils. The first stage is to boil the water when it is cold and put in two free-range chicken eggs with white outer shells and another egg with a slightly brown shell, then when the boiled water boils, wait for 3 minutes, then remove the two eggs and cool them in the air. The second treatment was carried out on two free-range chicken eggs with white shells and two free-range chicken eggs with slightly brown shells which were put into boiling water. After three minutes it is removed and cooled in the air. After the final treatment has cooled, peel the shell and then check the color of the boiled free-range chicken egg yolk. The result is village chicken eggs with white shells, the yolks are orange yellow and village chicken eggs with slightly brown shells, the yolks are pale yellow